The Influence on the Competency of Doctors in Medical Learning - Saleh, Nor Shela; Yaacob, Hashim Fauzy; Rosli, Mohd Shafie; Abu Bakar, Thuaibah; Md. Ali, Azlah (Journal of Social Transformation and Regional Development, 2019)
This study was conducted among the trainees who are undergoing medical learning or known as housemanship. The main issue of this research is the influence of the trainee doctor competency in medical education. There are four research objectives; to study the background, competency level, level of medical learning and the influence between competency and teaching of trainee doctor. This study was used questionnaires and a resulted 98 respondents were acquired. The majority of respondents aged are between 21 and 25 years old and married. The study also found that all the competencies and mastery of medical learning were well achieved. Researchers also found that there was a significant influence between competency and medical learning of a trainee doctor. However, researchers suggest that this study will be enhanced by researchers in the future so that the limitations and shortcomings of this study can be improved